High-temperature intrinsic ferromagnetism in heavily Fe-doped GaAs layers. (4th November 2020) - Kudrin, A V; Lesnikov, V P; Danilov, Yu A; Dorokhin, M V; Vikhrova, O V; Demina, P B; Pavlov, D A; Usov, Yu V; Milin, V E; Kuznetsov, Yu M; Kriukov, R N; Konakov, A A; et al.
Abstract: The layers of a high-temperature novel GaAs:Fe diluted magnetic semiconductor (DMS) with an average Fe content up to 20 at. % were grown on (001) i -GaAs substrates using a pulsed laser deposition in a vacuum. The transmission electron microscopy (TEM) and energy-dispersive x-ray spectroscopy investigations revealed that the conductive layers obtained at 180 and 200 ºC are epitaxial, do not contain any second-phase inclusions, but contain the Fe-enriched columnar regions of overlapped microtwins. The TEM investigations of the non-conductive layer obtained at 250 ºC revealed the embedded coherent Fe-rich clusters of GaAs:Fe DMS. The x-ray photoelectron spectroscopy investigations showed that Fe atoms form chemical bonds with Ga and As atoms with almost equal probability and thus the comparable number of Fe atoms substitute on Ga and As sites. The n -type conductivity of the obtained conductive GaAs:Fe layers is apparently associated with electron transport in a Fe acceptor impurity band within the GaAs band gap. A hysteretic negative magnetoresistance (MR) was observed in the conductive layers up to room temperature (RT). MR measurements point to the out-of-plane magnetic anisotropy of the conductive GaAs:Fe layers related to the presence of the columnar regions. The studies of the magnetic circular dichroism confirm that the layers obtained at 180, 200 and 250 ºC are intrinsic ferromagnetic semiconductors and the Curie point can reach up to at least RT in case of the conductive layer obtained at 200 ºC. It was suggested that in heavily Fe-doped GaAs layers the ferromagnetism is related to the Zener double exchange between Fe atoms with different valence states via an intermediate As and Ga atom.